The Functional Neuroanatomy of Letter-Speech Sound Integration and Its Relation to Brain Abnormalities in Developmental Dyslexia - Richlan, Fabio (Frontiers in Human Neuroscience, 2019)
This mini-review provides a comparison of the brain systems associated with developmental dyslexia and the brain systems associated with letter-speech sound (LSS) integration. First, the findings on the functional neuroanatomy of LSS integration are summarized in order to obtain a comprehensive overview of the brain regions involved in this process. To this end, neurocognitive studies investigating LSS integration in both normal and abnormal reading development are taken into account. The neurobiological basis underlying LSS integration is consequently compared with existing neurocognitive models of functional and structural brain abnormalities in developmental dyslexia—focusing on superior temporal and occipito-temporal (OT) key regions. Ultimately, the commonalities and differences between the brain systems engaged by LSS integration and the brain systems identified with abnormalities in developmental dyslexia are investigated. This comparison will add to our understanding of the relation between LSS integration and normal and abnormal reading development.